Hubungan Tingkat Pendidikan Ibu dan Pola Pemberian Makan dengan Kejadian Stunting di Wilayah Kerja UPT Puskesmas Pekauman Kota Banjarmasin - Siti Maulida Rahmah; Muhsinin Muhsinin; Sukarlan Sukarlan; Suci Fitri Rahayu (Jurnal Siti Rufaidah, 2025)
Stunting is a growth failure condition in toddlers caused by chronic malnutrition, particularly during the critical first 1,000 days of life. This condition is influenced by various factors, including maternal education and feeding practices. This study aims to analyze the relationship between maternal education level and feeding patterns with the incidence of stunting among toddlers in the working area of the Pekauman Community Health Center, Banjarmasin City. The research employed a quantitative design with a cross-sectional approach. The population consisted of mothers with toddlers, with 66 respondents selected through accidental sampling. Data collection was carried out using structured questionnaires and documentation studies related to children’s nutritional status. Data analysis was performed using univariate and bivariate methods, with the Spearman Rho test applied at a 0.05 significance level. The findings revealed a significant relationship between maternal education level and stunting incidence (p = 0.009), suggesting that lower levels of maternal education were associated with higher stunting rates. Conversely, feeding patterns did not show a statistically significant relationship with stunting (p = 0.081), although descriptive data indicated that inappropriate feeding practices were common among respondents. The majority of mothers in this study had basic education (elementary to junior high school), and a considerable number of toddlers were found to be stunted. Based on these results, it can be concluded that maternal education level plays an essential role in influencing stunting, while feeding patterns require further investigation with larger samples. The study recommends strengthening nutrition education and counseling programs for mothers, particularly those with low educational backgrounds, alongside regular monitoring of child growth and development by health professionals. Additionally, government efforts to expand access to health and nutrition information through easily accessible media are expected to contribute to stunting prevention and reduction strategies.